Grupos privados de mulheres na rede social facebook no contexto da pandemia da Covid – 19 no Brasil : estéticas da existência possíveis em meio à guerra - Visentin, Patrícia Menezes (2023)
The Covid-19 pandemic has brought numerous challenges to governments and populations that have been affected by it. Notably, developing countries – such as Brazil, suffer more intensely, due to social inequalities that unbridledly produce precarious conditions and subjectivations, combined with government measures that do not prioritize social well-being through actions in public and social policies – fundamental in global emergency situations. The daily difficulties experienced by social groups historically considered more vulnerable, such as women, LGBTQIA+, black people, people from the periphery, the homeless, among others, coexist before the start of the pandemic, but get exacerbated in crisis situations, inevitably generating instability in all sectors of life. In this work, the subaltern conditions experienced by Brazilian women in the course of the pandemic are taken as the guiding principle of this study. On the internet, the movement of groups in social networks promoted and put into practice by women is a social phenomenon since 2010 in Brazil; when in an attempt to denounce situations of abuse and violence, online forums and other initiatives were built on and off the internet, expanding discussions about situations experienced by women, generating points of tension between the public and private spheres. Private groups of women on the social network Facebook constitute the universe of this research, where women who are part of the 3 groups chosen for this work (Boleto +1, Deprê Club and Rede de Apoio as Mulheres) were invited to participate in semi-directed interviews. The interviews were guided by questions related to the trajectories experienced throughout the pandemic – contemplating different intersectionalities of women from 4 differente regions of Brazil, taking into account 4 domains of power – structural, cultural, disciplinary and interpersonal; involving the understanding of how the dynamics of the groups occurs – entry and permanence in them; the systematization of the impacts of these online groups on the lives of Brazilian women in the context of the Covid-19 pandemic in the country. The analysis of the interviews was carried out based on theoretical operators linked to 2 sources of thought: intersectionality, and authors who dialogue with intersectional feminism and discourse analysis based on Foucauldian archegenealogy. Intersectional feminism comprises the inclusion in its multiplicity, of women with their differences, particularities and specificities in the production of movements for rights, for freedom in its complex nuances and greater emancipation of women in the real possibility of a more equitable and (trans) formative world.The crossings and interpellations constituted from the social reading of gender – as a category of analysis and social division, are also fundamental for the construction of a critical look at the theme of this research, since, from the social naming of gender, a series of norms and places to be occupied and vacated through individual and collective resistance movements, are implied. Discourse analysis based on Michel Foucault's theoretical assumptions thoroughly complements the course of this work, by proposing the denaturalization of hegemonic discourses associated with more vulnerable populations and categories – such as women, based on the analysis of the complex power relations instituted in society. As for the results, two axes of analysis and discussion are presented, establishing a dialogue between them regarding the realities of the women interviewed, themes and experiences that were narrated and told in the interviews. The first axis is: 1) Bolsonaro government and authoritarianism in Brazil – pandemic and the ruling class government. This chapter is divided into two parts, namely: a) the rise of the right in Brazil in interface with political and social conjunctures in the election of Jair Bolsonaro to the Presidency of the Republic; and b) the denial of the pandemic and the precariousness of the population. This axis addresses conduct adopted by the federal government to manage the impacts of the pandemic on the population, with emphasis on the precarious state of resources for subsistence combined with the dismantling of public and social policies. The second axis is: 2) Online women's groups, chapter presented in two parts, namely: a) political ethical suffering, friendship policies and self-care; and b) women's loneliness, abandonment of the State and complete self-responsibility. It problematizes the functioning of the selected groups based on the dialogue between ethical-political suffering, friendship policies and self-care and helpless journeys of women, in view of the model of social organization based on the patriarchal system that radicalizes women to occupy social places inferiorized, based on power relations tempered by subjection. It is considered the importance of broadening discussions in different spaces about the possibilities for the circulation of narratives by women across the country, integrating different intersectionalities to better support policies that pay attention to their real needs and biopsychosocial realities, in interface with the political field in contemporary Brazil.